Association of supine and upright blood pressure differences with head-up tilt test outcomes in children with vasovagal syncope - Khalilian, Mohammad Reza; Nasehi, Mohammad Mehdi; Farahmandi, Fargol; Farahmandi, Farzaneh; Tahouri, Tahmineh; Parhizgar, Parynaz (Frontiers in Pediatrics, 2025)
IntroductionVasovagal syncope (VVS) is the most common childhood neurally mediated syncope. This study aims to define the different hemodynamic patterns in pediatric cases of vasovagal syncope and the difference between supine and upright blood pressure (orthostatic blood pressure), and other factors affecting them.MethodsMedical records of 88 children with normal laboratory and subclinical tests referred to Mofid Hospital for head-up tilt testing were retrospectively evaluated. Eighty-five children, 31 (36.5%) boys and 54 (63.5%) girls, aged 10.72 ± 3.52 years (median 10; range 4–17), with vasovagal syncope, were enrolled in the study. Age, sex, baseline heart rate, baseline blood pressure, orthostatic blood pressure, provoking factors, symptoms, and frequency were recorded. The test protocol included 10 min of supine rest followed by 30 min of upright positioning at a 70-degree angle. Subjects were divided into groups according to their differing hemodynamic patterns based on modified VASIS criteria.ResultsOur data showed a strong association between the difference in supine and upright blood pressure and positive HUTT results (p = 0.001). In the positive HUTT group, age had a higher probability of vasodepressor pattern in younger patients (p-value = 0.014). Also, a significant relationship is seen with the boys (p-value = 0.014, 0.038), which means that the male gender increases the probability of a positive tilt test.DiscussionOur study indicates that orthostatic blood pressure can predict HUTT in VVS children. Also, our results showed there is a higher chance of having a positive response to HUTT for the younger boys. Further studies in this field are warranted.